WORK ENVIRONMENT RELATIONS AND JOB PROMOTION AGAINST EMPLOYEE PERFORMANCE - Neli Hajar; Al-Munfarijah Al-Munfarijah; Laelatul Maghfiroh (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Employee performance is an important item to support the company's success in achieving its goals. A company will easily achieve its goals if a company has employees with quality and quantity performance, but different, if in the company there are employees with unqualified performance, then it is certain that the company will experience difficulties in achieving its goals. Employee performance will increase if at work, employees get an adequate work environment and compensation in the form of promotion. This study aims to determine the relationship between work environment and job promotion on employee performance at a PT in Brebes Regency. Population of data used in this research process is private university in kendal, amounting to 50. Questions in this questionnaire are closely related to the work environment and promotion from the perspective of employee performance perceptions. This study explains results that work environment has a relationship that does not affect employee performance improvement and job promotion has a relationship that has an influence on improving employee performance.